Morphological and mechanical behavior of chemically treated jute‐PHBV bio‐nanocomposites reinforced with silane grafted halloysite nanotubes. Issue 39 (21st June 2016) - Zainuddin, Shaik; Fahim, Abdullah; Shoieb, Shaik; Syed, Farooq; Hosur, Mahesh V.; Li, Dawen; Hicks, Chelsea; Jeelani, Shaik
ABSTRACT: In this study, at first, thin films of poly(3‐hydroxybutyrate‐ co −3‐hydroxyvalerate) (PHBV) nanocomposites were prepared by adding 1–3 wt % grafted halloysite nanotubes (G‐HNTs). Jute‐PHBV bio‐nanocomposites were then fabricated using these films and chemically treated jute fibers in a compression mold machine. The effect of treatment and modification on jute fiber and halloysite nanotubes (HNTs), and the change in their morphology was investigated using Fourier transform infrared (FTIR) spectroscopy, X‐ray diffraction (XRD), scanning and transmission electron microscopy (SEM, TEM). Flexural and thermomechanical properties were determined using a three‐point bend test and dynamic mechanical analysis (DMA). The results showed separation of fiber bundles with rough fiber surfaces, and grafting of silane coupling agents on fibers and HNTs after the chemical treatment. As a result, a strong bonding was established between the PHBV, G‐HNTs and jute fibers that lead to significant improvements in flexural and thermomechanical properties of jute‐PHBV bio‐nanocomposites. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43994. Abstract :